SPECTROFLUOROMETRIC HYDRODYNAMIC VOLTAMMETRY - THEORY AND PRACTICE - Compton, R; Fisher, A; Wellington, R; Winkler, J (1992)
A flow cell for simultaneous spectrofluorimetric voltammetry is described. The relevant theory is presented and the sensitivity of the technique evaluated. Experiments involving (a) the photooxidation of bis(benzylidene)acenaphthene and (b) the oxidation of p-phenylenediamine are shown to be in good agreement with theory. It is demonstrated that the technique can reveal the existence of trace quantities of electrode reaction intermediates and products and show previously unsuspected species participating in the electrode process. © 1992 American Chemical Society.